Jaką rolę odgrywają starsi Izraela w tekstach przedstawiających epokę Mojżesza? - Nawrot, Janusz (Poznańskie Studia Teologiczne, 2013)
The article presents the importance attributed to the term “the elders of Israel” by biblical authors. Exegesis of the relevant passages reveals in this expression some kind of social elite, separated from the rest of the common crowd, which, however, does not undertake any initiatives on its own, remaining absolutely faithful to the leader of the people and supporting him in action for the good of the community. Elected by the congregation for the purpose of organizing life within the community they also perform some ritual functions. As representatives of a sinful people before God, on behalf of that people “the elders of Israel” beg forgiveness for transgressions and by unquestionable obedience become guarantors of Israel’s courage in difficult circumstances. In situations of rebellion they also, as guardians of God’s law, manifest the value of all of God’s commandments. As participants of exceptional events they become a link between the secular community and the holiness of God. Keywords